Genesis of the 2008 global financial crisis and challenges to the neoclassical paradigm of finance - Szyszka, Adam (Economics and Business Review, 2011)
The paper presents the genesis of 2008 global financial crisis, discusses systemic changes in the financial world, and rises the question about the need for the new paradigm of finance in the lieu of the witnessed turbulent processes. A hypothesis is formulated that the neoclassical theory of finance lost its credibility due to systemic changes that have happened within institutions, markets, and instruments over the last three decades. It is suggested that the theory should be modified in line with dynamically changing financial environment. Conclusion is reached that an interdisciplinary approach is needed in the search for an adequate theory of finance. (original abstract)